(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the fundamental grammatical category of degrees of comparison, which applies to adjectives and adverbs in English. It explains the three main degrees: positive, comparative, and superlative, and provides clear examples of each, showing how they convey varying levels of quality, intensity, or extent. The article emphasizes the rules for forming these degrees, including common patterns for one-syllable and multi-syllable adjectives, as well as irregular forms like "good" (better, best). Additionally, it addresses the comparative and superlative forms of adverbs and highlights exceptions and irregularities in the language. The conclusion underscores the importance of understanding these degrees for effective communication, enhancing both clarity and nuance in expressing comparisons.